2021
DOI: 10.3390/cells10081950
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Spermine Metabolites Induce Apoptosis Associated with Increase of p53, caspase-3 and miR-34a in Both Neuroblastoma Cells, SJNKP and the N-Myc-Amplified Form IMR5

Abstract: Neuroblastoma (NB) is a common malignant solid tumor in children and accounts for 15% of childhood cancer mortality. Amplification of the N-Myc oncogene is a well-established poor prognostic marker in NB patients and strongly correlates with higher tumor aggression and resistance to treatment. New therapies for patients with N-Myc-amplified NB need to be developed. After treating NB cells with BSAO/SPM, the detection of apoptosis was determined after annexin V-FITC labeling and DNA staining with propidium iodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…Our study is in accordance with the recent work by Kanamori et al [42], who demonstrated that exogenous bovine serum amine oxidase and PA could induce apoptosis in cancer but not normal cells. However, we aimed to enhance the same PA-degrading pathway using small molecule drug substances to activate endogenous enzymes of PAs catabolism.…”
Section: Discussionsupporting
confidence: 94%
“…Our study is in accordance with the recent work by Kanamori et al [42], who demonstrated that exogenous bovine serum amine oxidase and PA could induce apoptosis in cancer but not normal cells. However, we aimed to enhance the same PA-degrading pathway using small molecule drug substances to activate endogenous enzymes of PAs catabolism.…”
Section: Discussionsupporting
confidence: 94%
“…In fact, most of the radioactivity is released from proteins (35-55%) and to a lesser extent from NA. RNase mainly releases Spm, whereas DNase releases mainly Spd with respect to the other two PAs[22,23]. Spm and Put were the main PAs bound to rRNA or to tRNA.…”
mentioning
confidence: 93%
“…These biogenic amines are ubiquitous across almost all living cells, from bacteria to plant and animal phyla, and are essential for life. In plants, the regulatory role in PCD of the main three aliphatic PAs, i.e., putrescine (Put), spermidine (Spd) and spermine (Spm), is reported by several articles [8,9,[15][16][17][18][19][20][21][22].…”
Section: Introduction Development and Pcdmentioning
confidence: 99%
“…In particular, the PA biosynthetic pathway is very active during cancer cell growth, and PA content is increased in tumor cells and tissues, such as breast, colon, skin, and prostate cancers. , Given the role of natural PAs in cancer, efforts have been made in search for strategies that target the PA metabolism, which might be useful for tumor treatment. , In this context, the main investigated strategies have been pointed to reduce intracellular PA concentration by inhibition of their synthesis or transport across cell membranes as well as through the use of analogues that interfere with PA metabolism. More recently, the strategy of exploiting PA-degrading enzymes to induce cancer cells death has been applied. , Indeed, the oxidative deamination of PAs catalyzed by some amine oxidases causes an over-production of aldehydes and hydrogen peroxide, which are cytotoxic and can damage cancer cells, causing apoptosis/necrosis and ultimately cell death. The induction of oxidative stress by increasing ROS has recently received great attention in anticancer therapies, and the effect of various anticancer drugs is based on the principle of oxidative stress-induced chemotherapy; for example, 2-methoxyestradiol induces mitochondrial production of hydrogen peroxide and subsequently activates c-Jun N-terminal kinase (JNK), resulting in apoptosis initiation …”
Section: Introductionmentioning
confidence: 99%